ANOMALY KEPENTINGAN ELIT DALAM KEBIJAKAN PUBLIC PRIVAT PARTNERSHIP (PPP) DI KOTA PEKANBARU - yandra, alexsander; utami, bunga chintia (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2019)
Regional Regulation No. 8 of 2018 concerning waste management with a partnership between the Pekanbaru City Government and the private sector, better known as the Public Private Partnership Policy (PPP) is full of problems. Termination of employment contract and training employees because it is not in accordance with the contract for failure of policy implementation. Carry out qualitative research with data publication techniques, literature studies and in-depth interviews. So the decision that the PPP Pemko Pekanbaru policy involving the private sector, namely PT. MIG in managing waste in the city of Pekanbaru does not run smoothly or effectively. The failure of the Pekanbaru City Government in a partnership pattern with the private sector caused by anomalies in the benefits of the political elite in interpreting policies.